Voices Within: Undergraduate Students’ Journey in Ethnocultural Qualitative Research - Sadaf Murad-Kassam; Alesia Au; Khadija Abdi; Esra Ben Mabrouk; Jordana Salma (International Journal of Qualitative Methods)
Collaborating in qualitative research with immigrant older women is a rich and rewarding learning opportunity for novice researchers as it expands their understanding of the lived experiences of ethnocultural communities. Undergraduate students with the same ethnocultural and linguistic backgrounds as research participants can build trust and rapport in research settings and, hence, are often hired onto research teams to assist with research activities. Undergraduate students learn in the field via hands-on experience and introductory theoretical training in qualitative methods, yet there is little guidance on effective mentorship strategies and considerations for this group of novice researchers. This paper reflects on the experiences of two undergraduate student researchers (USRs) who were involved as research assistants in a qualitative research study on immigrant women’s experiences of aging in place in urban Canadian neighbourhoods. The undergraduate students learned to manage challenges in the field related to setting boundaries and emotional well-being, navigating the presence of family during interviews, and addressing the hesitancy of participants in the research process. This paper discusses strategies to enhance the qualitative research knowledge and participation of USRs who conduct research as insiders in ethnocultural communities. Knowledge generated from this paper will be useful in spurring forward the discussion on qualitative fieldwork training for undergraduate students.